Association Between Serum Aldehydes and Hypertension in Adults: A Cross-Sectional Analysis of the National Health and Nutrition Examination Survey - Zhu, Yongjian; Liu, Mingjing; Fu, Wanrong; Bo, Yacong (Frontiers in Cardiovascular Medicine, 2022)
Background Exposure to ambient pollutants and chemicals were found to be associated with increased risk of hypertension. However, the relationship between the increased aldehyde exposure and hypertension are still unclear. This study aimed to investigate the potential associations of serum aldehydes levels with prevalent hypertension. Methods A total of 1,733 U.S. adults with data on hypertension outcome and serum aldehydes measurement from the National Health and Nutrition Examination Survey 2013–2014 were included. The serum levels of aldehydes were measured via an automated analytical method using solid phase microextraction gas chromatography and high-resolution mass spectrometry. Multivariate logistic regression models were adopted to assess the associations between six selected aldehydes exposure (benzaldehyde, butyraldehyde, heptanaldehyde, hexanaldehyde, isopentanaldehyde, and propanaldehyde) and prevalence of hypertension. Results The mean age was 48.0 ± 16.7 years and an approximately equivalent of sex distribution was observed (female 49.9%). There seems to be a numerically higher level of hexanaldehyde in participants with hypertension when compared to participants without hypertension (2.6 ± 3.9 ng/mL vs. 2.3 ± 1.1 ng/mL). After adjusting for potential confounders, the odds ratio (OR) for hypertension was 2.15 [95% confidence interval (CI): 1.33–3.51] in participants from the highest quartile of serum hexanaldehyde concentration in comparison to those from the lowest quartile. Subgroup analyses and sensitivity analyses showed generally similar results. Conclusion In summary, current evidence suggested that increased serum hexanaldehyde level was positively associated with prevalent hypertension in U.S. adults.